Serum ferritin, serum nitric oxide, and cognitive function in pediatric thalassemia major - Septiana Nur Qurbani; Lelani Reniarti; Alex Chairulfatah (Indonesian Pediatric Society, 2017)
Background Hemolysis and repeated blood transfusions in children with thalassemia major cause iron overload in various organs, including the brain, and may lead to neurodegeneration. Hemolysis also causes decreased levels of nitric oxide, which serves as a volume transmitter and slow dynamic modulation, leading to cognitive impairment.Objective To assess for correlations between serum ferritin as well as nitric oxide levels and cognitive function in children with thalassemia major.Â Methods This analytical study with cross-sectional design on 40 hemosiderotic thalassemia major patients aged 6âˆ’14 years, was done at the Thalassemia Clinic in Dr. Hasan Sadikin Hospital, Bandung, West Java, from May to June 2015. Serum ferritin measurements were performed by an electrochemiluminescence immunoassay; serum nitric oxide was assayed by a colorimetric procedure based on Griess reaction; and cognitive function was assessed by the Wechsler Intelligence Scale for Children test. Statistical analysis was done using Spearmanâ€™s Rank correlation, with a significance value of 0.05.Results Abnormal values in verbal, performance, and full scale IQ were found in 35%, 57.5% and 57.5%, respectively. Serum nitric oxide level was significantly correlated with performance IQ (P=0.022), but not with verbal IQ (P=0.359) or full scale IQ (P=0.164). There were also no significant correlations between serum ferritin level and full scale, verbal, or performance IQ (P=0.377, 0.460, and 0.822, respectively).Conclusion Lower serum nitric oxide level is significantly correlated to lower cognitive function, specifically in the performance IQ category. However, serum ferritin level has no clear correlation with cognitive function.